Basic Data on Relapse Conditions of Mental Disabilities (People with Mental Disorders) in Kebumen District, Central Java Indonesia - Agustin, Ike Mardiati; Yusuf, Munawir; Herdaetha, Adriesti; Wibowo, Agung (Global Health Science Group, 2024)
Healing psychosis in people with mental disabilities (People with Mental Disorder) requires a long-term treatment process followed by potential recurrence or relapse with varying causal factors, both internal and external. This research aims to present a database obtained from various sources resulting from identification of mental disability relapse conditions (people with severe mental disorders) in Kebumen district. The research method uses analytical descriptive using a survey approach to the community Public health center database in the Kebumen district on 4545 sufferers of serious mental disorders who had been treated and received routine treatment at health service facilities, the data was analyzed univariately with frequency distribution. The results of the study showed that of 4545 people with mental disabilities (severe mental disorders) 2692 (64.51%) experienced relapses or recurrences spread across all Public health center areas in Kebumen district with 3 Public health centers that had the highest relapses being at Mirit 265 Public health center (9.84 %) of relapse cases, Sruweng Public health center 249 (9.24%) and Kebumen 1 Public health center 110 (4%). Recommendations from the results of this study can be used as basic data for further efforts to treat relapse or recurrence in people with serious mental disorders.